Glycosylation pattern analysis of glycoprotein hormones and their receptors. (January 2017) - Núñez Miguel, Ricardo; Sanders, Jane; Furmaniak, Jadwiga; Rees Smith, Bernard
Abstract : We have studied glycosylation patterns in glycoprotein hormones (GPHs) and glycoprotein hormone receptor (GPHR) extracellular domains (ECD) from different species to identify areas not glycosylated that could be involved in intermolecular or intramolecular interactions. Comparative models of the structure of the TSHR ECD in complex with TSH and in complex with TSHR autoantibodies (M22, stimulating and K1-70, blocking) were obtained based on the crystal structures of the FSH-FSHR ECD, M22-TSHR leucine-rich repeat domain (LRD) and K1-70-TSHR LRD complexes. The glycosylation sites of the GPHRs and GPHs from all species studied were mapped on the model of the human TSH TSHR ECD complex. The areas on the surfaces of GPHs that are known to interact with their receptors are not glycosylated and two areas free from glycosylation, not involved in currently known interactions, have been identified. The concave faces of GPHRs leucine-rich repeats 3–7 are free from glycosylation, consistent with known interactions with the hormones. In addition, four other non-glycosylated areas have been identified, two located on the receptors' convex surfaces, one in the long loop of the hinge regions and one at the C-terminus of the extracellular domains. Experimental evidence suggests that the non-glycosylated areas identified on the hormones and receptors are likely to be involved in forming intramolecular or intermolecular interactions.